The obesity stigma and its consequences on children’s social and emotional functioning: a literature review - Ν. Κορνηλάκη Αικατερίνη (Psychology: the Journal of the Hellenic Psychological Society, 2020)
Obesity does not only raise health concerns, it can also have serious psycho - logical consequences. As the prevalence and severity of childhood obesity is increasing research has focused on its psychosocial consequences on children’s functioning. There is a consensus among the researchers that the main source of these problems lies in the social stigmatism of obesity. The aim of this literature review is to present the development and the prevalence of obesity stigma and its consequences on children’s social and emotional life. In the first part the emergence and the developmental course of anti-fat bias are presented, its content and the research methods that have been developed for its study. In the second part the consequences of anti-fat bias on body dissatisfaction, low self-esteem, bullying and teasing behaviours and social marginalization are presented. The findings suggest that there is a widespread discrimination against the obese. The need for exploring potentially preventive factors and intervention efforts is discussed.